Amplifying the efficacy of ALA-based prodrugs for photodynamic therapy using nanotechnology - Lou, Liang; Zhou, Shizhe; Tan, Sijia; Xiang, Menghua; Wang, Wei; Yuan, Chuang; Gao, Liqian; Xiao, Qicai (Frontiers in Pharmacology, 2023)
5-aminolevulinic acid (ALA) is a clinically approved prodrug involved in intracellular Heme biosynthesis to produce natural photosensitizer (PS) Protoporphyrin IX (PpIX). ALA based photodynamic therapy (PDT) has been used to treat various malignant and nonmalignant diseases. However, natural ALA has disadvantages such as weak lipophilicity, low stability and poor bioavailability, greatly reducing its clinical performance. The emerging nanotechnology is expected to address these limitations and thus improve the therapeutic outcomes. Herein, we summarized important recent advances in the design of ALA-based prodrugs using nanotechnology to improve the efficacy of PDT. The potential limitations and future perspectives of ALA-based nanomedicines are also briefly presented and discussed.